Innovative Strategies for Peer Review - Barroga, Edward (Journal of Korean medical science, 2020)
Peer review is a crucial part of research and publishing. However, it remains imperfect and suffers from bias, lack of transparency, and professional jealousy. It is also overburdened by an increasing quantity of complex papers against the stagnant pool of reviewers, causing delays in peer review. Additionally, many medical, nursing, and healthcare educators, peer reviewers, and authors may not be completely familiar with the current changes in peer review. Moreover, reviewer education and training have unfortunately remained lacking. This is especially crucial since current initiatives to improve the review process are now influenced by factors other than academic needs. Thus, increasing attention has recently focused on ways of streamlining the peer review process and implementing alternative peer-review methods using new technologies and open access models. This article aims to give an overview of the innovative strategies for peer review and to consider perspectives that may be helpful in introducing changes to peer review. Critical assessments of peer review innovations and incentives based on past and present experiences are indispensable. A theoretical appraisal must be balanced by a realistic appraisal of the ethical roles of all stakeholders in enhancing the peer review process. As the peer review system is far from being perfect, identifying and developing core competencies among reviewers, continuing education of researchers, reviewer education and training, and professional engagement of the scientific community in various disciplines may help bridge gaps in an imperfect but indispensable peer review system.